Electronic band structure of carbon honeycombs. (June 2018) - Pang, Zhenqian; Gu, Xiaokun; Wei, Yujie; Yang, Ronggui
Abstract: In this article, we present the electronic properties of various carbon honeycombs (C-honeycombs) with different cell sizes and junction types based on ab initio calculations. Among the three typical C-honeycombs with junctions connected via the zigzag edge, the armchair edge, or the hybrid edges of graphene nanoribbons, it is found that the zigzag C-honeycombs and the hybrid ones exhibit metallic properties. However, the armchair C-honeycombs are metallic only if the number of atomic planes N of the graphene nanoribbon in the C-honeycomb sidewall follows N  =  3p+1, with p as an integer and are semiconducting for other N . For those semiconducting ones, the bandgap of the C-honeycomb is about 1.19 eV with the narrowest sidewall ( 5. 2 Å) and monotonically decreases to about 0.15 eV when the width is increased to 34.8 Å. The semiconducting nature of such C-honeycombs with nanometer size pores may be used for lightweight semiconductor in electronic devices or supercapacitor energy storage. As a comparison, we show that all boron honeycombs are metallic, and their electronic properties are independent of sidewall widths. Highlights: First theoretical prediction of electronic properties of carbon honeycombs. Tunable electronic bandgaps. Structural dependent semiconductive/metallic behavior.